A case of reversible cytotoxic lesion of corpus callosum (CLOCCs) secondary to septic encephalopathy caused by suspected enteric fever - Tamanna Yasmin Shena; Umme Kulsum Chy; Amina Sultana; Mohammad Omar Faruq (Bangladesh Critical Care Journal, 2023)
Abstract not available Bangladesh Crit Care J September 2023; 11 (2): 140-141